Den LeibKörper erforschen: Phänomenologische, geschlechter- und bildungstheoretische Perspektiven auf die Verletzlichkeit des Seins - Müller, Beatrice,; Spahn, Lea, (transcript, 2020)
Understanding physicality and the body as central dimensions of an embodied scientific practice – based on Anke Abraham's work while spawning new connections.